1992
DOI: 10.1111/j.1365-2133.1992.tb14851.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of cutaneous lupus erythematosus with acitretin and hydroxychloroquine

Abstract: A randomized, double-blind, multicentre study was performed to compare the efficacy of acitretin (50 mg/day) with hydroxychloroquine (400 mg/day) in 28 and 30 patients, respectively, suffering from cutaneous lupus erythematosus (LE). The study was carried out over an 8-week period. Improvement of facial LE lesions after treatment with acitretin and hydroxychloroquine was assessed using several clinical parameters. In the acitretin group there was marked improvement or clearing of erythema in 10/24 patients (42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0
6

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(102 citation statements)
references
References 12 publications
4
92
0
6
Order By: Relevance
“…In one previous multicenter, randomized, controlled, doubleblind trial, Ruzicka et al compared acitretin with hydroxychloroquine in 58 patients with discoid or subacute cutaneous lupus. Both medications were effective in ϳ50% of the patients, but the incidence of side effects was higher in the acitretin group (26).…”
Section: Discussionmentioning
confidence: 93%
“…In one previous multicenter, randomized, controlled, doubleblind trial, Ruzicka et al compared acitretin with hydroxychloroquine in 58 patients with discoid or subacute cutaneous lupus. Both medications were effective in ϳ50% of the patients, but the incidence of side effects was higher in the acitretin group (26).…”
Section: Discussionmentioning
confidence: 93%
“…Additional treatment was not considered in 4 patients because they benefited from the first-line treatments. There was no significant difference between systemic isotretinoin and oral antimalarial treatments in terms of efficacy in DLE treatment (17). However, as far as the side effects are concerned, systemic isotretinoins can lead to dose-dependent telogen effluvium, and therefore oral antimalarials are superior to systemic isotretinoins.…”
Section: Discussionmentioning
confidence: 85%
“…A randomized, multi-center, double-blind study reported that in patients with CLE, the effectiveness of 50 mg acitretin/daily was comparable to that of the HCQ 400 mg/daily, which is the gold standard (46 % compared to 50 %) [18]. Overall, the results of case reports on isotretinoin and acitretin show an effectiveness of 60-80 % [18]. Alitretinoin also appears to bring about improvement in SCLE, DLE, and SLE.…”
Section: Oral Retinoidsmentioning
confidence: 98%
“…They are effective in 50-80 % or more of patients, and are thus considered the first-line treatment [12,18]. The mode of action of these substances has not been fully explained, although their effect is presumably due to immunomodulatory effects, such as influencing antigen presentation, stabilizing lysosomes, and suppression of the toll-like-receptor signal transduction pathway (especially TLR9) [12].…”
Section: Antimalarial Drugsmentioning
confidence: 99%